Gambaran Faktor Risiko Kejadian Pterygium pada Pasien di Poliklinik Mata Rumah Sakit Umum Daerah Tabanan - I Putu Baskara Adi Dananjaya; Ni Wayan Widhidewi; Ni Nyoman Sunariasih (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
Pterygium is a degenerative and invasive fibrovascular growth of the conjunctiva that extends to the cornea in a triangular shape with an apex in the corneal area. The incidence of pterygium in Indonesia is still relatively high as much as 13,1% with the highest prevalence found in Bali at 25,2%. The aim of this study was to determine the risk factors for the occurrence of pterygium including age, gender, and place of residence that could affect the occurrence of pterygium at the Eye Polyclinic of Tabanan Hospital and was conducted from January 2022 – August 2022. The study used descriptive design with a cross-sectional approach. The number of subjects was 102 patients that have met the inclusion and exclusion criteria. This study used a secondary data from medical records of pterygium patients in Eye Polyclinic of Tabanan Hospital. The result showed that the incidence of pterygium in the Eye Polyclinoc of Tabanan Hospital was obtained among as many as 84,3% of the subjects. The early elderly group in the range of 46 – 55 years were 36 (35,3%) subjects, 77 (75,5%) of the subjects were women, and 65 (63,7%) of subjects lived in rural areas. It is hoped that this research can be used as aadditional information, and for the agency that is the location of the research, which is the Eye Polyclinic of Tabanan Hospital to improve the recording of medical records so that the information obtained is mor accurate.